2021
DOI: 10.1111/arcm.12659
|View full text |Cite
|
Sign up to set email alerts
|

The rise of the cosmetic industry in ancient China: Insights from a 2700‐year‐old face cream

Abstract: Cosmetics have a long history in China, but their origins remain unclear. Cosmetic industry potentially originated in the , but little is known about the early manufacture and use of cosmetics. The Liujiawa site, located on the southern edge of the Loess Plateau in northern China, was the late capital of the ancient Rui state in the early to mid-Spring and Autumn Period. During the excavation, a sealed small and exquisite container with suspected cosmetic use was unearthed from tomb M49 belonging to a male ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It was quite a small constituent state, and its study drew little attention prior to the excavation of the Liangdaicun site and Liujiawa site. Studies have shown that inhabitants of the Rui State may have had an effective social structure and developed aesthetic tastes, with evidence gained from advanced techniques in metallurgy (Chen et al 2009) and from ruminant adipose fat as a matrix for cosmetic-making (Han et al 2021). However, little is known about the lifestyle and dietary production activities of the residents of the Liujiawa site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was quite a small constituent state, and its study drew little attention prior to the excavation of the Liangdaicun site and Liujiawa site. Studies have shown that inhabitants of the Rui State may have had an effective social structure and developed aesthetic tastes, with evidence gained from advanced techniques in metallurgy (Chen et al 2009) and from ruminant adipose fat as a matrix for cosmetic-making (Han et al 2021). However, little is known about the lifestyle and dietary production activities of the residents of the Liujiawa site.…”
Section: Discussionmentioning
confidence: 99%
“…Many artefacts have been unearthed at both sites (So, 2019), e.g. the early bronze-iron bimetallic techniques (Chen et al 2009) and cosmetics of moonmilk and ruminant adipose fat at the Liujiawa site (Han et al 2021). However, dietary studies have been lacking.…”
Section: The Archaeological Context Of the Liujiawa Sitementioning
confidence: 99%
“…Archaeological study has shown that cosmetics were used in ancient Egypt from approximately 3000 B.C. [ 1 ], and their uses in China can also date back to approximately 2700 years ago [ 2 ]. Nowadays, the cosmetic industry is thriving.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the cosmetic industry is thriving. The global cosmetics industry was valued at more than $500 billion in 2017 and is growing rapidly every year [ 2 ]. The consumption concept of “green beauty” also promotes a tendency to purchase cosmetic products of natural origin [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were used to disperse and apply bodily decorations and to soothe and heal surface wounds. Chemical analysis has very recently revealed that a pot buried with a Chinese nobleman some 2,700 years ago held a skin cream made from ruminant adipose fat mixed with monohydrocalcite, a mixture that was probably foundational to China's cosmetics at that time [1]. With the rise of civilisations, oils and waxes gradually became used in skincare, first among the Egyptians, then in traditional pharmacopoeia.…”
Section: Introductionmentioning
confidence: 99%